ANALISA PENGARUH STORE LAYOUT, MERCHANDISE ASSORTMENT, & PRICING TERHADAP PURCHASE INTENTION DI TOKO YAMAHA MELODIA MUSIK SURABAYA - azarya ekando anit yayang (Jurnal Strategi Pemasaran, 2015)
This study aimed to analyze the effect of store layout, merchandise assortment, pricing to purchase intetion in Melodia Yamaha Music Store. This study will be conducted by distributing questionnaires to 100 respondents consumer Yamaha Music Melodia. Analysis technique used is the technique of quantitative analysis using SPSS analytical methods or PASW (Predictive Analytics Software).